The efforts of Algerian scholars in serving the Moroccan manuscript During the 19th century" Mushrifies scientists as a model " - zahid alaoui, mwlay (The Algerian Historical Journal, 2026)
The Algerian scholars who immigrated to Morocco when the French occupation entered their country formed an important part of the Moroccan elite of scholars and thinkers. Thanks to their various writings and varied knowledge, these people contributed to enrich the Moroccan manuscript heritage with a significant stockpile of books and literature which focused on addressing a set of issues that concerned the state and society in Morocco during the nineteenth century. Additionally, official and private libraries in Morocco include a large number of manuscripts produced by Algerian writers, which dealt with various areas of knowledge such as history, jurisprudence, literature, politics, translation, and science. Al-Msharafi family scholars have played an integral part in these efforts through the large number of manuscripts they left behind, which received great and special interest among the political and scientific elite in Morocco. In this modest paper, we try to investigate how far Algerian productions contributed to the Moroccan manuscript via analyzing and evaluating the number of manuscripts they left in Morocco; to identify the fields of the knowledge covered by these manuscripts; to recognize the context and perspective from which these scholars started their work, and to determine the the scientific value of these manuscripts as well as their historial and cultural significance.